The Comparison of Antioxidant Activity of Ethanol Extract of Fruit, Seeds and Leaves of Yellow Pumpkin (Cucurbita moschata D.) using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) Method - Rahmatillah, Annie; Rohmana, Vivin Marwiyati; Mahendra, Andika Dwi; Puspita Sari, Mawar Dela; 'Arifah, Zainul (Poltekkes Kemenkes Gorontalo, 2025)
Yellow pumpkin (Cucurbita moschata D.) has various compounds that can be used as antioxidants, such as tocopherol, carotene, and phenolics. This research aims to determine which parts of the plant have potential as antioxidants by comparing the antioxidant activity of fruit, leaves, and seeds. Antioxidant activity measurements were carried out using the DPPH method by comparing the absorbance of the control and the absorbance of the sample to determine the percentage of antioxidant activity and IC50 value of each sample. From the measurement results, the IC50 values for pumpkin leaves, seeds, and fruit were 182.85 ppm, 57.04 ppm, and 90.88 ppm, respectively. Based on these results, leaves have the highest antioxidant activity compared to seeds and fruit. The results of this study show that pumpkin fruit and seeds have lower antioxidant activity than leaves. The results of this study show that pumpkin leaves had lower antioxidant activity than seeds and flesh.